Complete γ-th Moment Convergence for Weighted Sums Under WOD Setup - Qian Zhang; Yi Wu (Journal of Mathematics)
By utilizing the Rosenthal-type maximal moment inequality and truncation method, we mainly investigate the complete γ-th moment convergence for weighted sums of widely orthant dependent random variables in this paper. Some sufficient conditions of complete moment convergence are obtained, which generalize some corresponding ones of negatively orthant dependent random variables in the literature.